Effect of Some Demographic Changes on Some Oral Immune Aspects in Periodontal Disease Patients - AL-Mafraji , Fatima. H.; Alaubydi, Mouruj. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Periodontal diseases (PD) are worldwide diseases of humans either in childhood or adults. The present study aimed to find the correlation between some demographic and saliva immunological factors including the determination of saliva TLR-2, IL6, CRP, and α- amylase in patients with periodontal diseases. For this purpose, 60 patients out of which 33were males and 27 were females participated in this study from different Dental treatment Centers (Amirya Specialized Dental Center and Almaamon Specialized Dental Center ) in Baghdad/ Iraq, for the period starting from November / 2021 to February / 2022. Both age ranges for patients and control are (13-70) years, and patients’ mean ages are 34.29±15.01. Additionally, the control specimens were collected randomly from 40 apparently healthy people. The results of some demographic parameters revealed that there were no significant differences between males 55.0% and females 45.0% in PD. As well as, periodontal disease is not directly associated with rising smoking among patients or non-smoking individuals with PD. Acidic oral pH is not significantly found in most PD patients 47.1% and control subjects 66.7%, simultaneously, smoking may not be associated with acidic oral saliva directly. Other tests in concern with PD patients are considered to be very important in many aspects, firstly interleukin (IL6) recorded high non-significant mean occurrence results in both patients’ 50161± 63869 ng/l and control 52087 ± 62756 ng/l groups. Secondly, C-reactive protein (CRP) as IL6, recorded a non-significant increase in the saliva of PD patients at 0.537 ± 0.607 mg/l and control at 0.607  ±  0.266 mg/l. Toll-like receptor-2 (TLR-2) is the third immune parameter measured in saliva which recorded significant differences between PD patients 7.384  ±  4.031 ng/ml and control 5.313  ±  3.106 ng/ml, simultaneously. Then the fourth saliva parameter is α-amylase the results recorded a significant difference between PD patients 2.444  ±  1.870 ng/ml and control 1.041  ±  1.044 ng/ml. Also, the results showed that there was no correlation between measured demographic and immunological parameters.